A High-Frequency-Compatible Miniaturized Bandpass Filter with Air-Bridge Structures Using GaAs-Based Integrated Passive Device Technology - Zhi-Ji Wang (Micromachines, 2018)
This paper reports on the use of gallium arsenide-based integrated passive device technology for the implementation of a miniaturized bandpass filter that incorporates an intertwined circle-shaped spiral inductor and an integrated center-located capacitor. Air-bridge structures were introduced to the outer inductor and inner capacitor for the purpose of space-saving, thereby yielding a filter with an overall chip area of 1178 μm × 970 μm. Thus, not only is the chip area minimized, but the magnitude of return loss is also improved as a result of selective variation of bridge capacitance. The proposed device possesses a single passband with a central frequency of 1.71 GHz (return loss: 32.1 dB), and a wide fractional bandwidth (FBW) of 66.63% (insertion loss: 0.50 dB). One transmission zero with an amplitude of 43.42 dB was obtained on the right side of the passband at 4.48 GHz. Owing to its miniaturized chip size, wide FBW, good out-band suppression, and ability to yield high-quality signals, the fabricated bandpass filter can be implemented in various L-band applications such as mobile services, satellite navigation, telecommunications, and aircraft surveillance.